Tumor characteristics and prognosis in women with pregnancy‐associated breast cancer. Issue 7 (4th December 2017) - Johansson, Anna L.V.; Andersson, Therese M.‐L.; Hsieh, Chung‐Cheng; Jirström, Karin; Cnattingius, Sven; Fredriksson, Irma; Dickman, Paul W.; Lambe, Mats
Abstract : There is evidence of poor prognosis in women with pregnancy‐associated breast cancer (PABC) diagnosed during pregnancy or within 2 years of delivery. Using a large, population‐based cohort, we examined clinicopathologic features and survival in women with PABC. A cohort of women diagnosed with invasive breast cancer between 1992 and 2009 at ages 15–44 years was identified in the Swedish Cancer Register and the Breast Cancer Quality Registers. Dates of childbirths for each woman were retrieved from the Swedish Multi‐Generation Register. Age‐standardized distributions of tumor stage (tumor size, nodal status, metastasis), Elston grade and ER/PR/HER2 status were compared between nulliparous women and women with breast cancer during pregnancy and up to 10 years postdelivery. Adjusted hazard ratios for all‐cause mortality rates among patients were estimated using Cox regression. We identified 1, 661 nulliparous women with breast cancer, 778 women with PABC (97 during pregnancy, 270 within first and 411 within second year postdelivery) and 3, 598 during 2–10 years postdelivery. Compared to nulliparous women, women with PABC, and especially women diagnosed 0–12 months after delivery, had more advanced T and N stage, and higher proportions of ER/PR negative, HER2 positive and triple‐negative tumors. Increased hazard ratios were observed in women diagnosed within 5 years of delivery after adjustment for age, year, education and region. Following additional adjustment for tumor characteristics, the hazard ratios were attenuated and nonsignificant. The poorer prognosis observed in women with PABC appears to be largely explained by more adverse tumor characteristics at diagnosis. Abstract : What's new? Women who get breast cancer during or shortly after pregnancy fare worse than those whose cancer doesn't coincide with pregnancy. To help understand why, these authors collected data on a population based cohort, comparing tumor characteristics for childless women, women with pregnancy‐associated cancer, and women diagnosed more than 2 years after pregnancy. Pregnancy‐associated breast cancers, they discovered, often were more challenging to treat from the moment of discovery. More of them are hormone receptor negative, higher grade, and advanced stage. Thus, the worse outcome appears to be explained by more adverse tumor characteristics at diagnosis.